InGaN-based red light-emitting diodes: from traditional to micro-LEDs. (15th December 2021) - Zhuang, Zhe; Iida, Daisuke; Ohkawa, Kazuhiro
Abstract: InGaN-based LEDs are efficient light sources in the blue–green light range and have been successfully commercialized in the last decades. Extending their spectral range to the red region causes a significant reduction in LED efficiency. This challenge hinders the integration of red, green, and blue LEDs based on III-nitride materials, especially for full-color micro-LED displays. We review our recent progress on InGaN-based red LEDs with different chip sizes from hundreds to tens of micrometers, including the epitaxial structures, device fabrication, and optical performance (peak wavelength, full-width at half-maximum, light output power, efficiency, temperature stability, and color coordinates).